A comparison of two snapshot studies half a century apart suggests stability in a Pacific Northwest winter forest bird community - Clements, Nolan M.; Robinson, W. Douglas (Frontiers in Bird Science, 2024)
Populations of many North American bird species have declined throughout the past half century. The majority of studies quantifying these declines have analyzed counts of birds taken during spring and summer, not during the season of scarcity, winter. We re-surveyed seven large study plots in Douglas -fir (Pseudotsuga menziesii) forests initially surveyed in winter during the late 1960s in the Oregon Coast Range, USA. We compared density estimates, observed species richness and vegetation structure within plots, and inspected aerial photography to describe changes in landscape-level landcover. To assess potential drivers of change, we reviewed historical climate data and explored patterns of abundance associated with forest age. Observed species richness was greater in the modern surveys. Abundances of four of the six most common bird species appeared to be similar to or slightly lower than 50 years ago as the historical point estimates usually fell within or above 95% confidence intervals generated from our analyses. We found no clear associations with changes in bird communities and forest structure, climate, or forest age. The historical data are unique in providing point estimates of abundance for the entire bird community on each study plot. Yet, some uncertainties in accuracy of the historic counting methods could still influence interpretation of multi-decadal changes in apparent abundance. We conclude that this Pacific Northwest bird community was relatively stable in its abundances of the most common forest-dwelling species and that largely the communities are still intact.Additional production of precisely repeatable surveys of winter bird communities are needed in all habitats to adequately characterize long-term population dynamics during the season of scarcity.